Detailed anatomy of the retaining ligaments of the mandible for facial rejuvenation. Issue 9 (September 2016) - Kang, Mu Sam; Kang, Hyun Gu; Nam, Yong Seok; Kim, In-Beom
Abstract: Purpose: To present anatomical characteristics of three true ligaments of the mandible and better understanding of jowl formation. Materials and methods: Facial dissections were performed in 10 fresh cadavers (20 hemifaces) using 2.5 magnifying surgical loupes. Mental ligament, medial mandibular ligament, and mandibular osteocutaneous ligament were identified as thick fibrous tissue originating from the mandible. Results: The location of the mental ligament was 9.1 ± 2.8 mm lateral to the midline and 8.4 ± 3.8 mm superior to the inferior border of the mandible. The medial mandibular ligament was located 28.5 ± 4.9 mm lateral to the midline and 8.4 ± 2.7 mm superior to the inferior border of the mandible. The mandibular osteocutaneous ligament was located 51.1 ± 4.5 mm lateral to the midline and 9.1 ± 3.1 mm superior to the inferior border of the mandible. Conclusions: We investigated location and tension of two unfamiliar ligaments in the mandible, the mental and medial mandibular ligaments medial to the mandibular osteocutaneous ligament, and confirmed them as true ligaments by histology. Our findings suggest that the cause of the jowl formation is mainly descent of the cheek fat compartments, but not laxity of mandibular osteocutaneous ligament.